Small activating RNA activation of ATOH1 promotes regeneration of human inner ear hair cells. Issue 3 (1st March 2022) - Zhang, Yong-Li; Kang, Moorim; Wu, Jian-Cheng; Xie, Meng-Yao; Xue, Ruo-Yan; Tang, Qi; Yang, Hua; Li, Long-Cheng
ABSTRACT: The loss of inner ear hair cells leads to irreversible acoustic injury in mammals, and regeneration of inner ear hair cells to restore hearing loss is challenging. ATOH1 is a key gene in the development and regeneration of hair cells. Small activating RNAs (saRNAs) can target a gene to specifically upregulate its expression. This study aimed to explore whether small activating RNAs could induce the differentiation of human adipose-derived mesenchymal stem cells into hair cell-like cells with a combination of growth factors in vitro and thus provide a new strategy for hair cell regeneration and the treatment of sensorineural hearing loss. Fifteen small activating RNAs targeting the human ATOH1 gene were designed and screened in 293 T and human adipose-derived mesenchymal stem cells, and 3 of these candidates were found to be capable of effectively and stably activating ATOH1 gene expression. The selected small activating RNAs were then transfected into hair cell progenitor cells, and hair cell markers were examined 10 days after transfection. After transfection of the selected small activating RNAs, the expression of the characteristic markers of inner ear hair cells, POU class 4 homeobox 3 (POU4F3) and myosin VIIA (MYO7A), was detected. Human adipose-derived mesenchymal stem cells have the potential to differentiate into human hair cell progenitor cells. In vitro, small activating RNAs were able to induce the differentiation of hair cell progenitor cells into hair cell-like cells. Therefore, RNA activation technology has the potential to provide a new strategy for the regeneration of hair cells. Graphical Abstract: uf0001